Availability of Support and Quality of Life of Parents of Children with Autism Spectrum Disorders in Pandemic Conditions - Kovačić, Zoran M.; Cvijetić Vukčević, Marija M.; Nikolić, Gordana I. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Due to the COVID-19 pandemic, children with autism spectrum disorders and their parents faced numerous challenges related to health care, education and daily functioning, while available support was limited and often inadequate. The aim of this paper was to examine the differences in subjective quality of life and the support available to parents of children with autism and parents of typically developing children during the state of emergency declared due to the COVID-19 pandemic, as well as to explore the existence of an association between quality of life and the quality of support. The sample consisted of 39 parents of children with autism and 28 parents of children of typical development, fom both genders. To assess the subjective quality of life of parents, a short version of the Brunnsviken Brief Quality of Life Scale was used, while the quality of available support was measured using a scale specifically constructed for the purposes of this research. The results indicated that during the state of emergency, parents of typically developing children received better support from the health system and had more free time than parents of children with autism. In terms of quality of life, no statistically significant differences were found between the two groups of parents in any of the examined areas, nor in the overall quality of life. No association between quality of life and the quality of available support was found for either group of parents. The obtained results highlight the need to address the specific needs of families of children with autism in times of uncertainty, such as during a pandemic. These findings can inform future interventions aimed at providing support that is better aligned with the needs of both children and parents in similar circumstances.